The Influence of Product Class Knowledge and Environment Hostility to Relative Advantage with The Mediating Effect by Attitude Toward Change - Palumian, Yonathan; Atmajaya, Wong Norissa Leticia; Hoe, Anthony (LPPM STMIK Mardira Indonesia, 2024)
Small and medium enterprises (SMEs) are one of the fastest growing industries in Indonesia. This study aims to explore the effect of Attitude Toward Change on Relative Advantage of SMEs. The sample of this study is entrepreneurs domiciled in East Java who have a role as decision-makers, especially entrepreneurs who make management changes with the adoption of technology, such as changes using Enterprise Resource Planning (ERP) or other simple software. Data collection in this study was done by distributing questionnaires online and offline via e-mail, telephone, WhatsApp, and SME exhibitions in Malang and Surabaya. The questionnaire data will be processed using Smart PLS version 4.0 for further analysis. The results of the study show that the existence of Product Class Knowledge is usually achieved because of the feeling of threat from other competitors in the business world, or commonly called Environment Hositility. This research also proves the importance of mediation of attitude towards change in achieving a relative advantage of SME